Interface Engineering of Aluminum-magnesium Compounds. (2015) - Förster, W.; Binotsch, C.; Awiszus, B.; Dietrich, D.; Nickel, D.
Abstract: To combine the low density of magnesium with the corrosion resistance of aluminum in one component, a joint processing has gained scientific interest. It has been shown, that Al-Mg compounds and components with the material combination AlMgSi1/MgAl3Zn can be produced successfully by hydrostatic co-extrusion and forging. The interface region consists of the two phases β (Al3 Mg2 ) and γ (Al12 Mg17 ) with a significant lower ductility than the basic materials. Because of this brittle property the interface is fragmented due to stress condition during further forming. Thus, the durability of the components is limited. To address this problem the influence of an additional heat treatment on the interface was investigated by applying Differential Scanning Calorimetry (DSC). The aim of this study was to investigate if a phase transformation occurs in the temperature range up to 400 °C and whether it can be measured. Due to the small interface volume of the extruded strands, it is difficult to gather significant data on a phase transformation. Nevertheless, there are indications that phase transformations are possible at a lower temperature range. This might be an opportunity to design a more ductile interface and thus to improve the component properties.